Partnership Model between PT Alam Sinar and the Local Community in Gampingan Village, Pagak Subdistrict, Malang Regency - Ainindri, Qanisma; Pratiwi, Poerwanti Hadi; Budiman (Universitas Muhammadiyah Surakarta, 2025)
Partnerships between corporations and local communities play a crucial role in promoting inclusive and sustainable development, especially in areas directly affected by industrial activities. However, the implementation of such partnerships often fails to reflect the principles of equality, transparency, and active community participation. This study is part of a community service initiative aimed at analyzing the partnership model between PT Alam Sinar and the local community in Gampingan Village, Pagak Subdistrict, Malang Regency. It also evaluates the benefits, supporting factors, and challenges of the partnership by comparing conditions before and after the program was implemented. This research employs a qualitative approach with a case study design. Data were collected through observation, in-depth interviews, and documentation. Informants were selected purposively, including the village head, CSR representatives from the company, and community beneficiaries. The community service team acted as facilitators during the assessment process, participatory discussions, and reflection sessions involving both residents and the company. Findings indicate that the partnership is implemented through corporate social responsibility (CSR) programs focused on skills training, job creation, waste management, and the development of basic infrastructure. The benefits observed cover economic, social, and environmental aspects. Nevertheless, several challenges remain, such as limited community involvement in decision-making, suboptimal communication, and a lack of support from the district government. This study recommends strengthening community capacity, optimizing the role of village authorities, and developing a more inclusive, adaptive partnership model that responds to the actual needs of the local population.